Vertical GaN junction barrier Schottky diodes with near-ideal performance using Mg implantation activated by ultra-high-pressure annealing. (23rd September 2022) - Khachariya, Dolar; Stein, Shane; Mecouch, Will; Breckenridge, M. Hayden; Rathkanthiwar, Shashwat; Mita, Seiji; Moody, Baxter; Reddy, Pramod; Tweedie, James; Kirste, Ronny; Sierakowski, Kacper; Kamler, Grzegorz; et al.
Abstract: We report a kV class, low ON-resistance, vertical GaN junction barrier Schottky (JBS) diode with selective-area p-regions formed via Mg implantation followed by high-temperature, ultra-high pressure (UHP) post-implantation activation anneal. The JBS has an ideality factor of 1.03, a turn-on voltage of 0.75 V, and a specific differential ON-resistance of 0.6 mΩ·cm 2 . The breakdown voltage of the JBS diode is 915 V, corresponding to a maximum electric field of 3.3 MV cm −1 . These results underline that high-performance GaN JBS can be realized using Mg implantation and high-temperature UHP post-activation anneal.